Percepción sobre aguas residuales, residuos sólidos y calidad de vida de la población de Belén, Loreto, 2023 - Escobar Torres, Royce Kent (2024)
The objective of this investigation was to know the perception of wastewater, solid waste and quality of life of the population of the district of Belén, whose hypothesis was to determine if there is a relationship between the aforementioned variables, with the quality of life of the population. The population considered in this study was from 6 communities in the lower area of Belén, of a total of 16,123 inhabitants distributed in 2,648 homes, the sample was determined in 102 inhabitant’s heads of family. According to the results, the perception of the population on the studied variables does not affect their quality of life, the same ones who enjoy good health, economically, the little they obtain from their economic activities, provides them with the necessary conditions to live in peace and harmony. family, in their neighborhood environment among others. Similarly, it does not perceive environmental impacts and, if any, do not affect it. The reliability coefficient of the instrument used in the investigation was 0.76.